2015
DOI: 10.1007/s40843-015-0078-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and constitution of the binary system iridium-boron

Abstract: GPa [2] (48 GPa (0.5 N) [3]) or 26.6 GPa (39.3 GPa (0.5 N)) [2] with rather different hardness values due to the anisotropic crystal structure (for details on the crystal structure of W 1−x B 3 , see [4]). Vicker's hardness measurements on the boron richest iridium boride IrB 1.35 revealed a load independent value of 18.2 GPa (at 9.81 N) but 49.8 GPa at 0.49 N [5] and at such low loads the hardness is therefore comparable with bulk samples of ReB 2 . Quite high hardness values were also recorded for IrB 1.1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Furthermore, the investigations show that β-Ir 4 B 5 possesses a phase width and could therefore be labeled as β-Ir 4 B 5± x , as Zeiringer et al also suggested for other iridium borides. 10 However, in the following, we use the idealized formula β-Ir 4 B 5 . Figure 3 shows the structure, which can be described as stacking of alternating puckered boron layers (B, B′) and puckered iridium layers (A, A′) in the stacking sequence ABA′B′ in the c direction of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the investigations show that β-Ir 4 B 5 possesses a phase width and could therefore be labeled as β-Ir 4 B 5± x , as Zeiringer et al also suggested for other iridium borides. 10 However, in the following, we use the idealized formula β-Ir 4 B 5 . Figure 3 shows the structure, which can be described as stacking of alternating puckered boron layers (B, B′) and puckered iridium layers (A, A′) in the stacking sequence ABA′B′ in the c direction of the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Iridium–iridium distances in the framework range from 2.7332(5) to 2.9489(4) Å, which is similar to the iridium–iridium distances in other borides and metallic iridium. 10,26,28,61,62 Whereas the boron atoms B2 at the edge of the ribbons are coordinated by four iridium and two boron atoms, the boron atoms B1 have four close boron neighbors and four iridium atoms, leading to an 8-fold coordination (4 Ir + 4 B). The bond lengths of Ir–B within the iridium cage range from 2.128(8) to 2.249(11) Å and within the trigonal prism from 2.108(19) to 2.249(11) Å, which is slightly shorter than the sum (2.25 Å) of the covalent radii of the B atom ( r = 0.84 Å) and the Ir atom ( r = 1.41 Å).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations